Power loss of the chain drive in tandem bicycles - Smit, A.; van der Zwaard, S.; Janssen, I.; Janssen, T. W. (Journal of Science and Cycling, 2023)
Introduction: Tandem cycling is a Paralympic sport, in which two cyclists ride on one tandem bicycle. The front rider (pilot), is responsible for the steering, braking, changing gears, and tactics. The back rider (stoker), has a visual impairment and is responsible for responding to changes in cadence and generating power. As the average difference in finish time between obtaining a medal and becoming 4th was 0.5% at the Tokyo 2020 Paralympics for tandem cycling track and road time trial events, much time and effort in the competitive preparation is focused on enhancing individual and team performance. One way to increase performance is by minimizing power losses of the chain drive, which consists of two chains in tandem cycling, the primary and secondary chain. This study aimed to determine the mechanical power loss due to the chain drive of a race tandem bicycle and whether power losses in the chain drive are different for the pilot and stoker. Also, the effect of chain wheel size on power loss was studied.